Eosinophilic esophagitis improved by the discontinuation of sublingual immunotherapy for aeroallergens: a case report - Monzani, Alice; Cerutti, Marta; Curto, Sara; Lovaste, Sara; Coppola, Marta; Mercalli, Francesca; Saettone, Silvia; Rabbone, Ivana (Frontiers in Pediatrics, 2024)
Introduction: Eosinophilic esophagitis (EoE) is a chronic, immune-mediated inflammation of the esophagus, characterized by symptoms related to esophageal dysfunction, resulting from severe eosinophilic infiltration of the esophageal mucosa. It is common in atopic subjects and food antigens have been identified as the most common triggers. However, a seasonal variation in EoE prevalence, correlated with air pollen levels, is reported, suggesting that also aeroallergens may play a role. Little is known about the interplay between EoE and concomitant atopy treatment for aeroallergens.We describe the case of an 11-year-old boy who presented dysphagia, vomiting, drooling, and chest pain while eating meat, developed 15 months after receiving sublingual immunotherapy (SLIT) for Alternaria (SUBLIVAC®). He underwent esophagogastroduodenoscopy (EGD) revealing severe eosinophilic predominant inflammation (100 eos/HPF), consistent with the diagnosis of EoE, not improving at the EGDs performed after both omeprazole and topical corticosteroids treatment, despite symptom improvement. Afterward, immunotherapy was switched from sublingual to injective form. At the EGD performed 1 month later, macroscopic examination of the esophageal mucosa was normal and eosinophilic infiltration was significantly decreased (5-10 eos/HPF).Conclusions: SLIT may induce EoE by chronic antigenic exposure of oral mucosa in patients with a robust allergic susceptibility: while attenuating the IgE-mediated immune reactions, the progressive contact with the causative allergen might induce a chronic stimulation of the immune system with the consequent activation of tissue eosinophils. Our data suggest monitoring patients receiving SLIT for EoE symptoms and to discontinue SLIT on their earlier appearance, possibly as a first-line treatment.